2011
DOI: 10.1074/jbc.m111.270561
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-99a Inhibits Hepatocellular Carcinoma Growth and Correlates with Prognosis of Patients with Hepatocellular Carcinoma

Abstract: Background: microRNA-99a markedly decreases in HCC. Results: microRNA-99a expression correlates with HCC patients' survival, and microRNA-99a restoration suppresses HCC growth in vitro and in vivo by targeting IGF-1R and mTOR. Conclusions: microRNA-99a could be prognosis predictor and tumor suppressor for HCC. Significance: Reveal the important role of microRNA-99a in HCC development and provide prognosis predictor and therapeutic approach for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
198
2
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(214 citation statements)
references
References 53 publications
13
198
2
1
Order By: Relevance
“…The miRNA of other potential tumor suppressors has been found to target several components of the IGF-signaling pathway; for example, miR-615-5p, which was previously reported by our group to directly target IGF-2 (20). Focusing on the gatekeeper of the IGF-axis, IGF-1R, several miRNAs, including miR-145 and miR-99a, have been found to act as tumor suppressors in HCC through direct targeting of IGF-1R (21,22). Notably, it was recently reported that miR-486-5p directly targets IGF-1R in lung cancer (23).…”
Section: Microrna-486-5p Enhances Hepatocellular Carcinoma Tumor Suppmentioning
confidence: 99%
“…The miRNA of other potential tumor suppressors has been found to target several components of the IGF-signaling pathway; for example, miR-615-5p, which was previously reported by our group to directly target IGF-2 (20). Focusing on the gatekeeper of the IGF-axis, IGF-1R, several miRNAs, including miR-145 and miR-99a, have been found to act as tumor suppressors in HCC through direct targeting of IGF-1R (21,22). Notably, it was recently reported that miR-486-5p directly targets IGF-1R in lung cancer (23).…”
Section: Microrna-486-5p Enhances Hepatocellular Carcinoma Tumor Suppmentioning
confidence: 99%
“…miR-99a is found to be the sixth most abundant microRNA in the miRNome of normal human liver but is markedly down-regulated in HCC [41] . miR-99a dramatically suppresses HCC cell growth in vitro by inducing the G1 phase cell cycle arrest.…”
Section: Mirna-99mentioning
confidence: 99%
“…Furthermore, protein levels of IGF-1R and mTOR are found to be inversely correlated to miR-99a expression in HCC tissues. miR-99a inhibits IGF-1R and mTOR pathways, and subsequently suppresses the expression of cell cycle-related proteins including cyclin D1 in HCC cells [41] . Recent research suggested that miR-99a can target Argonaute-2 (Ago2) to inhibit tumor growth and obstruct the function of miR-21, thus relieving the inhibition of the phosphatase and tensin homolog (PTEN) gene imposed by miR-21 [42] .…”
Section: Mirna-99mentioning
confidence: 99%
“…Pharmacological or genetic inactivation of Notch signaling will provide insights into the role of Notch signaling in miR-99a-mediated cardioprotection. Furthermore, direct target genes of miR-99a for cardioprotection have not been identified, although the miR-99a targets for tumor suppression, 26,27) DNA damage response, 28) and wound healing 29) have been reported. Searching for direct target genes of miR-99a in cardiomyocytes will advance our understanding of the mechanisms whereby miR-99a protects cardiomyocytes from oxidative injury.…”
Section: Article P422mentioning
confidence: 99%